MSP w gospodarce opartej na wiedzy - nowe wyzwania i szanse na dynamiczny rozwój - Kuźniar, Katarzyna (SMEs in the Knowledge-based Economy - New Challenges and Chances for Dynamic Development, 2008)
Small and medium-sized enterprises (SMEs) are a very heterogeneous group of businesses usually operating in the service, trade and manufacturing sectors. They include a wide variety of firms. Some of them are dynamic, innovative and growth-oriented while others are satisfied to remain small and perhaps family owned. SMEs are often classified by the number of employees and/or by the value of their assets. The main purpose of the paper is to assess the significance of development of SMEs for competitiveness of domestic economy in the international scale. It is also an attempt of answering two questions: what new chances gives the knowledge-based economy to SMEs relative to large enterprises and what challenges should be undertaken by SMEs in terms of creating and developing the knowledge-based economy.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 125-135